Exploring Effective Teaching Strategies: Simulation Case Studies and Indigenous Studies at the University Level - Norman, Heidi (The Australian Journal of Indigenous Education, 2004)
Abstract This paper explores teaching strategies for communicating complex issues and ideas to a diverse group of students, with different educational and vocational interests, that encourage them to develop critical thinking, and explores pedagogies appropriate to the multidisciplinary field of Aboriginal studies. These issues will be investigated through discussion of a successful simulation case study, including the setting up, resourcing, conducting and debriefing. The simulated case study was an assessed component of the new elective subject, Reconciliation Studies, offered at the University of Technology Sydney. In 2003 students participated in a role-play based on events in relation to the development of the Hindmarsh Island Bridge. Students were assigned roles as stakeholders where they researched and then role-played, through their assigned characters, the multilayered and complex dimensions of this recent dispute. Students were required to reflect critically on the cultural, economic, legal and political issues that were pertinent to their stakeholder and explore the underlying racial, ethical and moral grounds for their particular standpoint. I argue that teaching strategies such as these can contribute to locating Indigenous Australian perspectives and experiences as critical within the professional profiles and practice skills of Australian university graduates.